Influence of serum levels of vitamins A, D, and E as well as vitamin D receptor polymorphisms on micronucleus frequencies and other biomarkers of genotoxicity in workers exposed to formaldehyde - Ladeira, Carina (2016)
Background/Aim: Formaldehyde is classified as carcinogenic to humans, making it a major concern, particularly in occupational settings. Fat-soluble vitamins, such as vitamins A, D, and E, are documented as antigenotoxic and antimutagenic and also correlate with the cell antioxidant potential. This study investigates the influence of these vitamins on genotoxicity biomarkers of formaldehyde-exposed hospital workers. Methods: The target population were hospital workers exposed to formaldehyde (n = 55). Controls were nonexposed individuals (n = 80). The most used genotoxicity biomarkers were the cytokinesis-block micronucleus assay for lymphocytes and the micronucleus test for exfoliated buccal cells. Vitamins A and E were determined by high-performance liquid chromatography with a diode array detector (HPLC-DAD) and vitamin D receptor (VDR) polymorphisms by real-time PCR. Results: Significant correlations were found between genotoxicity biomarkers and between vitamins A and E in controls. Multiple regression showed that vitamin A was significantly associated with a higher mean of nucleoplasmic bridges (p < 0.001), and vitamin E was significantly associated with a decreased frequency of nuclear buds (p = 0.045) in the exposed group. No effect of vitamin D was observed. The VDRBsmI TT genotype carriers presented higher means of all the genotoxicity biomarkers; however, we found no significant associations. Conclusions: The study suggests that vitamin levels may modulate direct signs of genotoxicity.